Act of Mar. 14, 1776, ch. VII, 1775-76 Mass. Act 31 - 32, 35 - (:unkn) unknown (General Publisher, 1776)
Recommended the disarming of persons who are “notoriously disaffected to the cause of America, or who refuse to associate to defend by arms the United American Colonies.”
--
Keywords: POSSESSION - DANGEROUS PERSONS